Screening of some sorghum genotypes for resistance to sorghum midge, Stenodiplosis (= Contarinia) sorghicola Coqillet (diptera: Cecidomyiidae) under gedarif rainfed conditions - Suliman, E. H.; Salman, H. A.; Mohamed, E.I.; Salih, S. A.; Ali, A.E.; Adam, M. H. M.; Hassan, M. K.; Mohamed, A. H.; Elnour, O. A.; Kannan, H. O. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Preliminary experiments were conducted at Northern area, Gedarif State during seasons of 2002-03, 2006-07.Where as advanced trials during 2008/2009 to 2012/2013 at northern and Southern areas. The objective was to evaluate selected sorghum genotypes for sorghum midge resistance. A total of 3000 accessions were obtained from Gene Bank Resources. Resistant genotype, DJ 6514 (Resistant Check already released in 2007) was obtained from International Crops Research Institute for the Semi-Arid Tropics (ICRISAT). Result showed that the midge damage rating was significantly different among genotypes. The midge damage rating scores ranged between, 1.3- 8.6; 1.1- 9.2; 1.4- 9.0; 1.1 – 9.4; and 1.2- 9.2 for all seasons (2008/09; 2009/10; 2010/11; 2011/12 and 2012/13). However, the lowest midge damage rating was recorded by DJ 6514 (Resistant check), followed by P₁ 570162 (Hag Abbakar); GBM 30 (Early Feterita); Wad Baco; and Safra (1.4; 1.5; 1.5, 1.6 and 1.7), respectively. Genotypes, P₁ 570162 (Hag Abbakar); GBM 30 (Early Feterita); Wad Baco; Safra and Harerai showed lowest % yield loss and performed similar to the resistant check (14.2; 14.5; 14.5; 17.0 and 17.3%), respectively. The combined analysis showed that a significant difference was observed between genotypes. The genotypes were significantly different in panicle types, compact and semi-compact headed genotypes showed lower % glumes coverage (1.3- 4.5%), while semi-compact headed genotypes ranged between 5.5 – 7.8%. Genotypes, Wad Baco; P₁ 570162 (Hag Abbakar); GBM 30 (Early Feterita); Safra; Wad Ahmed; Harerai and Wad Akar showed the shortest glumes coverage (1.3; 1.3; 1.5; 1.5; 1.6; 1.7 and 1.8 %). Compact headed genotypes recorded lowest midge density (6.5 adults/ 5 heads), while the semi-compact headed genotypes were recorded 15.7 adults/ 5 heads compared with others types of heads.